2021
DOI: 10.3389/fonc.2021.671853
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA FGD5-AS1 Facilitates the Radioresistance of Breast Cancer Cells by Enhancing MACC1 Expression Through Competitively Sponging miR-497-5p

Abstract: BackgroundLncRNA-FGD5-AS1, as an oncogene, participates in the development and progress of various cancers. However, the exact role and the molecular mechanisms by which FGD5-AS1 regulates radiosensitivity in breast cancer (BC) remains largely unknown.MethodsWe used X-Ray weekly-dose-increase method to establish radiation-resistance cell lines. Bioinformatics tools analyze the expression of FGD5-AS1 in breast cancer tissue and evaluated the relationship between FGD5-AS1 and clinic-pathological features. CCK-8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…FGD5-AS1 is significantly overexpressed in breast cancer tissues and cells and could promote the proliferation, glycolysis, migration, and invasion of BC cells by binding with miR-195-5p and removing the inhibitory effect on NUAK2 expression; moreover, silencing FGD5-AS1 leads to the opposite phenotype [ 45 ]. Li et al [ 23 ] also confirmed the above results and found that FGD5-AS1 can competitively bind with miR-497-5p, which promotes the expression of MACC1 and the radiotherapy tolerance of BC cells. Furthermore, FGD5-AS1 deficiency could promote breast cancer cell apoptosis and sensitize the cells to X-rays by activating the expression of BAX, Caspase 3, and Caspase 9 [ 23 ].…”
Section: Genital Systemmentioning
confidence: 66%
See 2 more Smart Citations
“…FGD5-AS1 is significantly overexpressed in breast cancer tissues and cells and could promote the proliferation, glycolysis, migration, and invasion of BC cells by binding with miR-195-5p and removing the inhibitory effect on NUAK2 expression; moreover, silencing FGD5-AS1 leads to the opposite phenotype [ 45 ]. Li et al [ 23 ] also confirmed the above results and found that FGD5-AS1 can competitively bind with miR-497-5p, which promotes the expression of MACC1 and the radiotherapy tolerance of BC cells. Furthermore, FGD5-AS1 deficiency could promote breast cancer cell apoptosis and sensitize the cells to X-rays by activating the expression of BAX, Caspase 3, and Caspase 9 [ 23 ].…”
Section: Genital Systemmentioning
confidence: 66%
“…Li et al [ 23 ] also confirmed the above results and found that FGD5-AS1 can competitively bind with miR-497-5p, which promotes the expression of MACC1 and the radiotherapy tolerance of BC cells. Furthermore, FGD5-AS1 deficiency could promote breast cancer cell apoptosis and sensitize the cells to X-rays by activating the expression of BAX, Caspase 3, and Caspase 9 [ 23 ]. These results indicate that FGD5-AS1 plays an important role in the progression of BC.…”
Section: Genital Systemmentioning
confidence: 66%
See 1 more Smart Citation
“…Li et al found that lncRNA FGD5-AS1 was overexpressed in breast cancer tissues and predicted poorer clinical characteristics and prognosis. 51 This study demonstrated that most m 6 A-related ln-cRNA FGD5-AS1 was associated with cisplatin resistance, by competitively binding to has-miR-362-3p in BRCA patients. In another case, Hu et al revealed that IGF2BP2 served as an m 6 A reader to regulate lncRNA DANCR, thereby promoting cancer stemness-like properties and pathogenesis.…”
Section: Lnc2m6a: a Web-based Resource For M 6 A-related Lncrnas In C...mentioning
confidence: 71%
“…The included studies in the current systematic review and meta-analysis were published between 2015 and 2020 and conducted in Canada and China. The sources of the malignant tumor included glioma ( 35 , 36 , 38 , 41 , 43 ), neck squamous carcinoma (HNSCC) ( 57 ), esophageal cancer (EC) ( 22 ), breast cancer ( 34 , 42 , 46 , 47 ), colorectal cancer ( 39 , 58 ), non-small cell lung cancer (NSCLC) ( 40 , 45 , 50 – 52 ), ovarian cancer (OC) ( 48 ), cardiac carcinoma ( 49 ), thyroid carcinoma ( 44 ), prostate cancer ( 54 ), and nasopharyngeal carcinoma (NPC) ( 37 , 56 ). Sample sizes included in these studies varied from 31 to 955 between the studies.…”
Section: Resultsmentioning
confidence: 99%